GENES DETERMINING THE SYNTHESIS OF LAVONOID AND MELANIN PIGMENTS IN BARLEY - O. Yu. Shoeva; K. V. Strygina; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
In addition to the green color caused by chlorophyll, grain and vegetative organs of barley can be colored by compounds of phenolic nature, such as melanins and lavonoids, which include anthocyanins, proanthocyanidins. Due to the wide biological activity of these pigmented compounds and their uncolored precursors in respect to plants and humans, there has recently been an increased interest in studying genes that determine pigmentation in plants. The gene network determining the synthesis of lavonoid pigments is the most studied one. Since the 1970s, structural genes that encode the enzymes of lavonoid metabolism, as well as regulatory genes that determine the tissue-speciic accumulation of these pigments in grain tissues, as well as in vegetative organs have been identiied and localized in the barley genome. The Ant1 and Ant2 genes, determining the accumulation of anthocyanins in grain pericarp, the Ant28 gene controlling the biosynthesis of proanthocyanidins (condensed tannins) in seed coat, as well as the HvMpc2, HvMyc2 and HvWD40 genes responsible for the accumulation of anthocyanins in the aleurone layer of barley grain have been determined. Melanins are less studied pigments of plants. Due to the complex structure and resistance to various solvents, the chemical nature of these pigments has not been established. However, due to the comparative analysis of transcriptomes in the colored and uncolored lemma and grain pericarp of barley near-isogenic lines, it was possible to identify the metabolic pathways underlying the formation of the melanin pigmentation. The proposed article reviews the results of the studies on the genetic control of barley coloration.